Analysis of the Difficulty Level of Students in Writing Stories in the Indonesian Language Subject in Grade IV of SDIT Harapan Umat Brebes (Lembaga Pengembangan Kinerja Dosen, 2025)
Education is a conscious and planned effort to create a learning atmosphere and learning process so that students actively develop their potential to have spiritual religious strength, self-control, personality, intelligence, noble character, and skills needed by themselves, society, nation and state (Law of the Republic of Indonesia). To realize the goals of national education, the curriculum is made as a guideline used in learning activities as regulated in Law of the Republic of Indonesia No. 32 of 2013 concerning National Education Standards. The purpose of this study is to describe the difficulties of students in writing stories in the Indonesian language subject of grade IV at SDIT Harapan Umat Brebes. This study uses a qualitative research type. The approach used in this study is qualitative research with a descriptive approach. The location of this research is SDIT Harapan Umat Brebes on Jl. Proklamasi KM. 03 Utara Islamic Center (In front of the Integrated Government Office), Brebes, Central Java, Indonesia 52212. Based on the research that has been done on the analysis of the level of difficulty of students in writing stories in the Indonesian language subject, it can be concluded that the level of ability of grade IV students in writing stories is still quite low. The difficulties faced by students in writing stories in the Indonesian language subject in grade IV SDIT Harapan Umat Brebes include several things, including students experiencing difficulties in determining the title of the narrative text, students' inability to arrange words into a story that is interconnected with each other.